Effects of Methods of Planting and Timing of Herbicide Application on the Economics of Lowland Rice in Badeggi, Nigeria - Audu, S.D; Haruna, I.M; Ibrahim, A. J; Ibrahim, S. O; Bakare, S. O (BADEGGI JOURNAL OF AGRICULTURAL RESEARCH AND ENVIRONMENT, 2024)
The experiment was conducted in 2021 and 2022 wet season at National Cereals Research Institute headquarters, Badeggi, Niger state (latitude 9o041 02.05’’N, longitude 0.6o011 3.31’’E) in the Southern Guinea Savannah Agro-Ecological Zone of Nigeria. To evaluate the cost-effectiveness of different planting methods and herbicide application timings on lowland rice production for farmers in the region. The experiment was laid out in a factorial experiment. The treatment consists of five sowing methods (broadcasting dry, broadcasting wet, dibbling wet, dibbling dry and transplanting) with two different timing of herbicide application. The 10 treatment combinations were laid out in a factorial experiment with a split-plot design with timing of herbicide application allocated to the main plot while sowing methods were designated to the sub-plot. Data were collected on Plant height, number of tillers, day to 50% flowering, day to maturity, number of seeds per panicle, seed yield per panicle, 1000-grain weight and grain yield per hectare. The result indicated that overall, the transplanting method of planting resulted in the significantly highest for all parameters, followed by the dibbling wet and dibbling dry methods. The broadcast method resulted in the poorest outcomes. Applying herbicide at 2 WAS resulted in better outcomes compared to 3 WAS. The transplanting method with herbicide application at 2 WAS resulted in the significantly highest grain yield, gross returns, and gross margin, making it the most profitable option.